CO and CO2 methanation over Ni/Al@Al2O3 core–shell catalyst - Le, Thien An; Kim, Jieun; Kang, Jong Kyu; Park, Eun Duck (Catalysis Today, 2020)
Core–shell Al@Al2O3, which was obtained by hydrothermal surface oxidation of Al metal particles, was used as the support in supported Ni catalysts for CO and CO2 methanation. The core–shell micro-structured support (Al@Al2O3) helped develop a highly efficient Ni-based catalyst compared with conventional γ-Al2O3 for these reactions. Moreover, the deposition–precipitation method was shown to outperform the wet impregnation method in the preparation of the active supported Ni catalysts. The catalysts were characterized using various techniques, namely, N2 physisorption, H2 chemisorption, CO2 chemisorption, temperature-programmed reduction with H2, temperature-programmed desorption after CO2 adsorption, X-ray diffraction, inductively coupled plasma-atomic emission spectroscopy, high-resolution transmission electron microscopy, and in situ diffuse reflectance infrared Fourier transform spectroscopy. Higher Ni dispersion when using Al@Al2O3 as the support and the deposition–precipitation method resulted in better catalytic performance for CO methanation. Furthermore, the higher density of medium basic sites and enhanced CO2 adsorption capacity observed for Ni/Al@Al2O3 helped increase catalytic activity for CO2 methanation.
Keywords: Catalytic performance; Co methanation; Inductively coupled plasma atomic emission spectroscopy; Ni catalysts; Precipitation methods; Situ diffuse reflectance infrared Fourier transform spectroscopy; Temperature-programmed reduction; Wet impregnation method; Al@Al2O3; CO methanation; CO2 methanation; deposition–precipitation method; Ni catalyst; γ-Al2O3